WordPress complete : learn how to build a beautiful and feature-rich website or blog with WordPress all on your own - Król, Karol (Packt Publishing, 2017)
Learn how to build a beautiful and feature-rich website or blog with WordPress all on your own. About This Book Learn how to build a WordPress site quickly and effectively, and how to create content that's optimized for publication on the web. Learn the basics of working with WordPress themes and plugins, and even create your own. Beginner-friendly layout and advice you can apply from day 1. Packed with screenshots and examples. Who This Book Is For This book is for anyone who wants to learn how to create a functional website, without having to hire a developer or a designer. The best thing about WordPress--the open source software that we're going to be using--is that it has a minimal learning curve and that everyone can master it quickly. No specific website building experience is required. Having said that, this book will also appeal to everyone who wants to get a bit more in-depth with WordPress development and start working on their own plugins and themes. What You Will Learn What WordPress is, where to get it, and how to launch your website quickly using it. How to publish your first content (a blog post or article). What the most important sub-pages of a quality website are, and how to create them in WordPress. How to upload multimedia content such as images, audio, and video. How to install and work with plugins and widgets. Where to find quality themes and how to install them. How to develop your own WordPress plugins and themes. In Detail WordPress Complete, Sixth Edition is a practical guide for everyone who wants to start their journey as an online publisher, website owner, or even a website developer. It takes you step-by-step through the process of planning out and building your site, and offers loads of screenshots and examples along the way. It's also a beginner's guide to theme and plugin development. This book begins with the basics of WordPress, followed by the different components that you as a developer will need to use to work swiftly and efficiently. The book starts by introducing WordPress to new readers in this field. You are then shown how to set it up, implement a blog, and use plug-ins and widgets. You'll use themes to make any website look and feel better and more original. You also learn how to create your own themes and perform testing to ensure your website is bug-free. You will also acquire some idea of how to use WordPress for non-blog-like websites. By the end of the book, you will feel confident enough to desi ...